Pembentukan Karakter pada Anak Usia Dini di Lingkungan Keluarga - nindiya, devi candra; indrawati, dwi; setyowati, rina insani; prawinda, raras ayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Character formation in early childhood is a necessity that must be done by parents as family leaders. Because all parents want their children to have good character in life. This descriptive qualitative research with literature study discusses the formation of character in early childhood in the family environment. The data analysis technique uses content analysis by sorting out data according to the research objectives. This paper produces several things as follows. First, the role of parents or family in character building for early childhood, among others: parents must be role models for children, parents must be able to show empathy for children, parents must use good moments to build children's character, parents can tell stories and life, parents must be able to show pride in children, parents must be able to teach children to control themselves, and parents must give children opportunities to practice character actions. Second, tips for parents or families to form early childhood with good character, including consistent, continuous, and consistent, because children are influenced by the environment, temperament, and character. Third, the program that can be offered to families to build character for early childhood is parenting. The types of programs include family gatherings, foundation classes, seminars, consultation days, field trips, home activities, cooking on the spot, bazaar day, mini zoo, and home education videos